Evaluation of Fractional CO2 Versus Long Pulsed Nd:YAG Lasers in Treatment of Hypertrophic Scars and Keloids: A Randomized Clinical Trial. Issue 10 (15th April 2020) - Tawfic, Shereen O.; El‐Tawdy, Amira; Shalaby, Suzan; Foad, Ahmed; Shaker, Olfat; Sayed, Safinaz S.; Metwally, Dina
Abstract : Background: Keloids and hypertrophic scars are challenging to both patients and physicians. They can be aesthetically disfiguring, functionally debilitating, and emotionally distressing. Lasers have introduced new mechanisms to improve scars both on aesthetic and symptomatic levels. Aim of Work: Comparing the efficacy of fractional CO2 laser, long‐pulsed Nd:YAG laser and their combination in the treatment of hypertrophic scars and keloids on clinical, histopathological, and biochemical basis. Patients and Methods: Thirty patients with hypertrophic scars and keloids were enrolled in the study. Three scars in each patient were randomly assigned to treatment modalities (i) Fractional CO2, (ii) Nd:YAG laser, (iii) Combined CO2 and Nd:YAG lasers. For each treatment area four sessions, 4–6 weeks apart were performed. Clinical evaluation was done before and 1 month following last session using the Vancouver Scar Scale (VSS) and the Patient and Observer Scar Assessment Scale (POSAS). Routine hematoxylin and eosin, Masson's trichrome, and Orcein stains were used to evaluate the appearance and pattern of dermal collagen and elastic fibers. Image analysis was used to quantitatively assess the density of collagen and elastic fibers. Biochemical evaluation of tissue level of transforming growth factor‐β I (TGF‐β I) and TGF‐β III was performed using enzyme‐linked immunosorbent assay studies. Results: Both VSS and POSAS showed significant improvement following treatment with the three used modalities. Collagen fibers showed significant improvement as regards appearance and pattern while it was insignificant as regards density. Elastic fibers density improvement was only significant in fractional CO2 (treatment area A). Hypertrophic scars showed more significant improvement with fractional CO2 laser, while in keloids there was no significant difference between the three modalities regarding improvement. Level of TGF‐β I showed significant reduction after treatment in all treatment modalities, while TGF‐β III levels showed insignificant elevation in all treatment modalities. Side effects were significantly higher in treatment area C (combined treatment). Conclusion: Long pulsed Nd:YAG laser is effective and safe treatment of hypertrophic scars and keloids. Fractional CO2 laser yields better improvement in hypertrophic scars, while in keloids both fractional CO2 and Nd:YAG lasers achieve comparable improvement. Combination in the same session did not add significant additional benefit and the side effects profile was higher. Limitations: small sample size and short follow‐up period. Lasers Surg. Med. © 2020 Wiley Periodicals, Inc.